2011
DOI: 10.1007/s10765-011-1009-8
|View full text |Cite
|
Sign up to set email alerts
|

An International Study of the Long-Term Stability of Metal–Carbon Eutectic Cells

Abstract: For high-temperature fixed points to be accepted as temperature references, it is of prime importance that their long-term stability is demonstrated. This evaluation is part of the CCT-WG5 high-temperature research project (Machin et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 3 publications
2
25
0
2
Order By: Relevance
“…The drift can in all cases be considered as negligible in comparison with the uncertainties of temperature determination. Earlier studies have already shown that the stability of HTFPs on the long term is ensured in case of the hybrid cell design [8,9] and this study shows clearly that, past the robustness issues with early designs, HTFP cells can be considered as reliable and efficient artefacts for comparisons. Each participant to this task (CEM, PTB, NPL, UME, LNE-Cnam) reported the assigned ITS-90 temperature of the melting transition realised with the circulating HTFP cells in their facilities.…”
Section: Dissemination Using Htfpsmentioning
confidence: 58%
“…The drift can in all cases be considered as negligible in comparison with the uncertainties of temperature determination. Earlier studies have already shown that the stability of HTFPs on the long term is ensured in case of the hybrid cell design [8,9] and this study shows clearly that, past the robustness issues with early designs, HTFP cells can be considered as reliable and efficient artefacts for comparisons. Each participant to this task (CEM, PTB, NPL, UME, LNE-Cnam) reported the assigned ITS-90 temperature of the melting transition realised with the circulating HTFP cells in their facilities.…”
Section: Dissemination Using Htfpsmentioning
confidence: 58%
“…The drift can in all cases be considered as negligible in comparison with the uncertainties of temperature determination. Earlier studies have already shown that the stability of HTFPs in the long term is ensured in case of the hybrid cell design [8,9] and this study shows clearly that, passed the robustness issues with early designs, HTFP cells can be considered as reliable and efficient artefacts for comparisons. Each participant to this task (CEM, PTB, NPL, UME, LNE-Cnam) reported the assigned ITS-90 temperature of the melting transition realised with the circulating HTFP cells in their facilities.…”
Section: Dissemination Using Htfpsmentioning
confidence: 58%
“…For this part of the project, mainly based on the significant experience of CNAM [3][4], the main objective is to develop references for radiation thermometry in participating NMIs seeking to establish a research capability in this field (WP2):  Encourage knowledge transfer in radiation thermometry for the realization of the ITS-90, by organizing training workshop and by establishing best practice guide.  Perform an inter-laboratory comparison of radiation thermometer calibration in order to improve calibration technique and to assess the uncertainties of measurements.…”
Section: Radiation Thermometrymentioning
confidence: 99%